2009
DOI: 10.1038/nrmicro1968
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces morphogenetics: dissecting differentiation in a filamentous bacterium

Abstract: During the life cycle of the filamentous bacteria Streptomyces, morphological differentiation is closely integrated with fundamental growth and cell-cycle processes, as well as with truly complex multicellular behaviour that involves hormone-like extracellular signalling and coordination with an extraordinarily diverse secondary metabolism. Not only are the bacterial cytoskeleton and the machineries for cell-wall assembly, cell division and chromosome segregation reorganized during sporulation, but the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
546
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 566 publications
(555 citation statements)
references
References 133 publications
3
546
1
5
Order By: Relevance
“…A-factor is a specific γ-butyrolactone that has been well studied in S. griseus [46]. Our analysis showed that many components in the A-factor signaling cascade are conserved in the five Streptomyces genomes, including at least seven gene families functioning in a chronological order (strep 1890, strep 2366, strep 3567, strep4078, strep2310, strep1012, and strep8592) [26]: strep1890 contains an A-factor receptor ArpA, which can block the expression of AdpA (strep3567) during the growth of vegetative mycelium. Upon the activation of A-factor biosynthesis by strep2366, A-factor is accumulated, which will release the expression of AdpA (strep3567), an ECF sigma factor that can trigger the downstream effector proteins that are essential for morphological differentiation (strep4078, strep2310, and strep1012) and secondary metabolism (strep8592) [47,48].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A-factor is a specific γ-butyrolactone that has been well studied in S. griseus [46]. Our analysis showed that many components in the A-factor signaling cascade are conserved in the five Streptomyces genomes, including at least seven gene families functioning in a chronological order (strep 1890, strep 2366, strep 3567, strep4078, strep2310, strep1012, and strep8592) [26]: strep1890 contains an A-factor receptor ArpA, which can block the expression of AdpA (strep3567) during the growth of vegetative mycelium. Upon the activation of A-factor biosynthesis by strep2366, A-factor is accumulated, which will release the expression of AdpA (strep3567), an ECF sigma factor that can trigger the downstream effector proteins that are essential for morphological differentiation (strep4078, strep2310, and strep1012) and secondary metabolism (strep8592) [47,48].…”
Section: Resultsmentioning
confidence: 99%
“…Streptomycetes are model organisms for developmental biology as they exhibit a complex life cycle similar to filamentous fungi, beginning with spore germination, followed by the growth of vegetative mycelium, and the formation of aerial hyphae [26]. Cell morphogenesis of streptomycetes is governed by a series of gene families such as fts, whi, ssg and mre [26].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations